2019
DOI: 10.1371/journal.pone.0212473
|View full text |Cite
|
Sign up to set email alerts
|

Nasal microbial composition and chronic otitis media with effusion: A case-control study

Abstract: Objectives Chronic otitis media with effusion (COME) in children can cause prolonged hearing loss, which is associated with an increased risk of learning delays and behavioural problems. Dispersal of bacterial pathogens from the nasal passages to the middle ear is implicated in COME. We sought to determine whether there is an association between nasal microbial composition and COME in children. Methods A case-control study of children aged 3 and 4 years was conducted. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Operational taxonomic units (OTUs) with Alloiococcus or Propionibacterium annotation were renamed. Dolosigranulum is known to be misclassified in the GreenGenes database as Alloiococcus [21]. BLAST search confirmed that the representative sequence matched Dolosigranulum in BLAST.…”
Section: Microbiota Analysismentioning
confidence: 63%
“…Operational taxonomic units (OTUs) with Alloiococcus or Propionibacterium annotation were renamed. Dolosigranulum is known to be misclassified in the GreenGenes database as Alloiococcus [21]. BLAST search confirmed that the representative sequence matched Dolosigranulum in BLAST.…”
Section: Microbiota Analysismentioning
confidence: 63%
“…In particular, Walker et al showed that the nasal microbiome in children with OME is composed of a higher abundance of pathogens, with a lower abundance of commensals as alpha-hemolytic Streptococci and Lactococcus. Moreover, cluster analysis revealed that profiles dominated by Corynebacterium, Streptococcus, or Moraxella were associated with COME, while healthy children had a more mixed bacterial profile with higher abundance of commensals [81].…”
Section: Otitis Media With Effusionmentioning
confidence: 98%
“…Nasopharyngeal microbiome is less diverse in children suffering from OME than in controls, as highlighted by two case-control studies [80,81]. In particular, Walker et al showed that the nasal microbiome in children with OME is composed of a higher abundance of pathogens, with a lower abundance of commensals as alpha-hemolytic Streptococci and Lactococcus.…”
Section: Otitis Media With Effusionmentioning
confidence: 99%
“…COME shares a similar clinical presentation but with the addition of continuous serous drainage, while CSOM features purulent drainage leaking from a perforated tympanic membrane or ventilation tube (Mittal et al, 2015; Schilder et al, 2016). Chronic OM etiologies tend to be more serious for patients, as frequent and/or persistent dysfunction of the Eustachian tube may lead to significant hearing loss, thereby negatively impacting language acquisition and behavioral development in children (Cripps and Kyd, 2003; Santos-Cortez et al, 2016; Walker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The various morphologies and presentations of OM disease [AOM, recurrent AOM (rAOM), CSOM, OME, and/or COM] is about as varied and dynamic as the bacterial, viral, and fungal microorganisms that contribute to OM pathogenesis. However, the research has well-established the link between rAOM and the major otopathogens S. pneumoniae , non-typeable Haemophilus influenza (NTHi), and M. catarrhalis , and these species are consistently found at higher levels of the NP in studies comparing the microbiota of rAOM and COME cases versus healthy controls (Lappan et al, 2018; Walker et al, 2019). Yet the presence of these same organisms, albeit at lower levels, in the controls suggest their potential role as endogenous pathobionts even in the absence of disease.…”
Section: Introductionmentioning
confidence: 99%